A Case Report of a Submental and Submandibular Space Infection - Santosh Kumar Subudhi1 , Subrat Kumar Padhiary1 , Harsh Mohan Pathak2 , Kalyan Sundar Pal3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
In most of the cases of space infections are secondary to an odontogenic infection. In space infection,spread occurs through the fascial plane because of the degradation of connective tissue by action of differentenzymes produced by microorganisms. Different factors like age, nutritional status of the host, host defense,virulence of the microorganism play an important role in the spread of the infection. Sometimes it may takethe fetal course if not treated on time because of its local and systemic complications. It should be treatedas an emergency condition to prevent its rapid progression leading to fatal outcome. Here the case reportdescribes an old lady suffering from fascial space infection and treated by incision and drainage. Incompleteremoval of any odontogenic infection may cause the recurrence of the infection or infection that may spreadto fascial spaces.